Decision Support System for Recipients of Cash Social Assistance using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) Method - Alfarisi Pasaribu, Ahmad; Saputra, Imam; Karim, Abdul (ADA Research Center, 2025)
Cash Social Assistance (BST) is assistance in the form of money provided to poor, disadvantaged, and/or vulnerable families affected by the Corona Virus Disease 2019 (COVID-19) outbreak. The amount of Cash Social Assistance is IDR 600,000/family/month. This Cash Social Assistance is a social safety net program of the Ministry of Social Affairs intended for poor and vulnerable families affected by Covid-19. This program is a special assignment assistance from the President. Social assistance for areas outside Jabodetabek is provided in the form of money, while for the Jabodetabek area it is provided in the form of basic necessities. The provision of BST assistance does not include recipients of the Family Hope Program (PKH), Staple Food Cards, and Pre-Employment Cards. To obtain the Cash Social Assistance (BST) funds, the government has set several criteria for which families can be determined and are entitled to receive the Cash Social Assistance (BST). These criteria will later help government agencies in determining which residents can be selected to receive the Poor Family Assistance Fund. Therefore, a government agency must have a Decision Support System for Cash Social Assistance (BST) recommendations using the Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) method, with the existence of a decision support system for determining Cash Social Assistance (BST) it is expected to run well, be on target, and be received by the entitled people. Thus, decision makers can compare the performance between the old system and the decision support system for determining BST funds using the Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) method without having to re-request data on families who will be given Cash Social Assistance (BST) funds.